Employee Engagement: A Literature Review - Ririn Yuzarni (Jurnal Manajemen Bisnis Performa, 2018)
ABSTRACT Employee engagement always an interesting issue anywhere around the globe, not only in entrepreneurship world, but also in everyday people. Along with these issues, the specific definition of “employee engagement” has always regenerated as well over time. Basically, the point of this literature research is to analyze the concept (definition) of employee engagement chronologically from numbers of journal and books related to usage of literature observation method. While the originality contribution of this research is about development of employee engagement’s definition chronologically. Certainly, this writing creates an originality contribution to development of employee engagement’s definition itself. The last point of this research is in form of conclusion, where employee engagement defined as cognitive state of employee which is really involved emotionally with showing positive behavior, such as enthusiasm, and concerned deeply to reach the organization or company’s goal.ABSTRAK  Keterlibatan karyawan selalu menjadi masalah menarik di mana saja di seluruh dunia, tidak hanya di dunia wirausaha, tetapi juga pada orang biasa. Seiring dengan masalah-masalah ini, definisi spesifik "keterlibatan karyawan" selalu diperbarui juga seiring waktu. Pada dasarnya, tujuan dari penelitian literatur ini adalah untuk menganalisis konsep (definisi) keterlibatan karyawan secara kronologis dari jumlah jurnal dan buku yang terkait dengan penggunaan metode observasi literatur. Sedangkan kontribusi orisinalitas dari penelitian ini adalah tentang pengembangan definisi keterlibatan karyawan secara kronologis. Tentu saja, tulisan ini menciptakan kontribusi orisinalitas untuk pengembangan definisi keterlibatan karyawan itu sendiri. Poin terakhir dari penelitian ini adalah dalam bentuk kesimpulan, di mana keterlibatan karyawan didefinisikan sebagai keadaan kognitif karyawan yang benar-benar terlibat secara emosional dengan menunjukkan perilaku positif, seperti antusiasme, dan sangat peduli untuk mencapai tujuan organisasi atau perusahaan.